2012
DOI: 10.1007/s10096-012-1594-x
|View full text |Cite
|
Sign up to set email alerts
|

The optimal aminoglycoside and its dosage for the treatment of severe Enterococcus faecalis infection. An experimental study in the rabbit endocarditis model

Abstract: Aminoglycosides are recommended for the treatment of Enterococcus faecalis infections, especially in severe and bacteremic infection. However, the optimal aminoglycoside or the optimal dosage remains uncertain. This study aimed to compare the activity of four aminoglycosides against E. faecalis (gentamicin, netilmicin, tobramycin, and amikacin) and two dosages of gentamicin. One clinical strain of E. faecalis was used to induce aortic endocarditis in the study rabbits. Each aminoglycoside was infused daily ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Animal models have not shown a superiority of high versus low doses of gentamicin in combination with penicillin [85], and clinical data reveal an increased nephrotoxicity for larger doses [86]. However, a recent study showed superiority of high doses of gentamicin (6 mg/kg/ day) over the standard one in the in vivo model of EFIE [87]. International guidelines recommend gentamicin at a dose of 3 mg/kg/day in three equally divided doses (t.i.d.)…”
Section: Treatment Optionsmentioning
confidence: 90%
“…Animal models have not shown a superiority of high versus low doses of gentamicin in combination with penicillin [85], and clinical data reveal an increased nephrotoxicity for larger doses [86]. However, a recent study showed superiority of high doses of gentamicin (6 mg/kg/ day) over the standard one in the in vivo model of EFIE [87]. International guidelines recommend gentamicin at a dose of 3 mg/kg/day in three equally divided doses (t.i.d.)…”
Section: Treatment Optionsmentioning
confidence: 90%
“…We would therefore need two routes (one of which would be for the continuous or intermittent administration of ampicillin by means of a perfusion pump) or a well-trained family member capable of performing (two or three times a day) these manipulations, in addition to the logistics inherent to the monitoring of levels. However, these recommendations are based on experimental studies [ 181 , 182 , 183 , 184 ], sometimes contradictory [ 185 , 186 ] possibly due to differences related to the different pharmacokinetics of the experimental model and humans. On the other hand, there are abundant studies that show the efficacy of single-dose administration of aminoglycosides, with excellent activity due to their prolonged post-antibiotic effect and much less renal toxicity [ 187 ].…”
Section: Outpatient Parenteral Antimicrobial Therapy (Opat)mentioning
confidence: 99%
“…We would therefore need two routes (one of which would be for the continuous or intermittent administration of ampicillin by means of a perfusion pump) or a well-trained family member capable of performing (two or three times a day) these manipulations, in addition to the logistics inherent to the monitoring of levels. However, these recommendations are based on experimental studies [177][178][179][180] , sometimes contradictory 181,182 possibly due to differences related to the different pharmacokinetics of the experimental model and humans. On the other hand, there are abundant studies that show the efficacy of singledose administration of aminoglycosides, with excellent activity due to their prolonged post-antibiotic effect and much less renal toxicity 183 .…”
Section: Outpatient Parenteral Antimicrobial Therapy (Opat) With the ...mentioning
confidence: 99%